IMPLEMENTASI AUGMENTED REALITY TATA SURYA MENGGUNAKAN METODE MARKER BASED TRACKING (STUDI KASUS : MI ASSA’ADAH) - Muhammad Fahmi Sidqi; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Education is a very important thing at this time to increase knowledge and as a support and ideals for the future. Therefore, now there are many technologies that promise lessons in it. With technology, it can provide positive benefits in the field of education. The technology in question is Augmented Reality. Augmented Reality is a technology that allows users to interact with virtual environments created by computers, so that users feel as if they are in the room. The purpose of the research is to create learning media that can display 3-dimensional objects using Augmented Reality. Researchers are devoted to the introduction of the solar system to children, the introduction of the solar system to children can stimulate the brain to imagine and train creativity. With the development of information technology, animal recognition facilities can be carried out using devices such as personal computers, laptops or smartphones. The development of Augmented Reality technology on smartphones will make it easier for early childhood to recognize several types of the solar system, especially in today's modern era where gadgets such as tablets and smartphones have been recognized by early childhood and kindergarten age children, which causes children to be more likes to play gadgets rather than studying with books. The design of the Augmented Reality application uses Unity software by designing markers made using CorelDraw and animal models that have been made with a 3D blender. The features in this application are several types of animals that are displayed in 3D and animation using Augmented Reality technology.